We Learn about the World Having Fun (2008)
In 2008 we launched the first set of toys for children to explore by themselves in a playful and emotional way some questions addressed in EAFIT Children's University: Car (a wooden vehicle), Keep it standing (children have the challenge of building a edification), Zoetrope (which gives life to a series of drawings and invites to make animations), and Settlers (a game of alliances and strategies to form a country).